Digitally Printed Liquid Metal Composite Antenna for Energy Harvesting: Toward Energy‐Autonomous Battery‐Free Wearable Bioelectronics. Issue 2 (9th December 2022) - Maranha, Miguel; Silva, André F.; Lopes, Pedro Alhais; de Almeida, Aníbal T.; Tavakoli, Mahmoud
Abstract: Rapid progress on wearable bioelectronics holds the promise for remote patient monitoring. However, there are concerns related with the use of batteries, including the need for frequent charging, user safety, and environmental pollution. The development of rapidly deployable battery‐free patches that harvest their energy from external sources is highly desired. Here, untethered battery‐free patches through far‐field energy harvesting are demonstrated. Taking advantage of a stretchable biphasic liquid metal‐based ink and digital fabrication techniques, that is, direct printing, and laser patterning, tailor‐made customized antennas are fabricated over various substrates, including polydimethylsiloxane, Kapton, and wound‐dressing medical‐grade adhesives. Folded dipole and planar inverted‐F antennas (PIFA) are evaluated and they are optimized for an over‐the‐body scenario. Compared to previous works that only show communication of data at <1 Hz, here, battery‐free acquisition and transmission of electrocardiogram (ECG) data at 100 Hz via Bluetooth is demonstrated. It is shown that using 3 parallel PIFA antennas, it is possible to harvest ≈10 mW at 30 cm from the transmitter, which is ≈7× the required power by the ECG circuit. This study proves the feasibility of next generation of battery‐free wearable biomonitoring patches/e‐textiles and demonstrates materials and methods for fabrication of optimized printed antennas. Abstract : Using digital printing methods, the authors present two different approaches in antenna fabrication and optimization. Conductive ink with liquid metal and silver flakes permits the antennas to have record‐breaking stretchability and excellent electromechanical coupling upon repetitive strain movements. Finally, an electrocardiogram belt with 100 Hz communication using Bluetooth, is entirely powered with the antenna's harvested energy.